Association between dietary index for gut microbiota and cardiovascular-kidney-metabolic syndrome: a population-based study - Long, Dan; Mao, Chenhan; An, Haoyu; Zhu, Ying; Xu, Yin (Frontiers in Nutrition, 2025)
BackgroundCardiovascular-kidney-metabolic (CKM) syndrome represents a major health threat globally. The newly proposed dietary index for gut microbiota (DI-GM), which quantifies dietary quality associated with gut microbiota diversity, may influence the risk of CKM syndrome. Therefore, this study examined the correlation between DI-GM and the prevalence of CKM syndrome, aiming to provide insights for preventive innovation and tailored treatment methods.MethodsThis cross-sectional study included 8,400 adults aged 20 years and older from the National Health and Nutrition Examination Survey (NHANES) 2007–2018. The potential association between the DI-GM score and CKM syndrome was evaluated using univariable and multivariable weighted logistic regression models, restricted cubic spline (RCS), and subgroup analyses.ResultsThe average age of the participants was 45.5 years, with 52.0% of the participants being male. A higher DI-GM score was significantly associated with a lower prevalence of CKM syndrome (OR = 0.87, 95% CI: 0.81 to 0.92, p <  0.001). The RCS analysis further confirmed a linear relationship between DI-GM score and CKM syndrome (p for nonlinear = 0.194). Furthermore, subgroup analysis indicated that sex potentially influenced the association between DI-GM and CKM syndrome (p for interaction = 0.004), with the protective effect being more pronounced among U. S. females.ConclusionDI-GM score exhibits an inverse correlation with the risk of CKM syndrome. Optimizing dietary patterns to improve DI-GM is associated with reduced risk of CKM syndrome.